PERANAN LEMBAGA SWADAYA MASYARAKAT (LSM) TERHADAP PENANGANAN KASUS TINDAK PIDANA KEKERASAN SEKSUAL PADA ANAK - Maurice Rogers; Arozatulo Mendrofa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
The role of non-governmental organizations (NGOs) in handling cases of sexual violence against children is very important. The role of NGOs in carrying out advocacy and other services for victims of sexual violence against children aims to fulfill children's rights as mandated in the child protection law. The method used in this research is normative legal research method. The writing of this research uses analysis of interpretation and syllogism to describe or explain the legal issues under study, provide comments and then make a conclusion on the results of the research with the help of theory. Based on the research and discussion carried out by the author, namely the role of non-governmental organizations in handling criminal cases of sexual violence against children, namely conducting legal advocacy against children as victims of sexual violence to fulfill their rights, besides that Non-Governmental Organizations (NGOs) provide assistance to victims such as counseling services to strengthen and provide a sense of security for victims of rape who have suffered trauma and mental and psychological consequences so that counseling is very helpful for mental recovery and restoring the victim's self-confidence.